Pengaruh Mobilisasi Terhadap Tingkat Nyeri Pada Pasien Post Operasi Orif di RSUD Karsa Husada Batu - Nabila Silva Sabrina; Arief Bachtiar; Marsaid Marsaid (Universitas Malahayati Lampung, 2025)
ABSTRACT Postoperative pain is a common complication experienced by patients, including those undergoing Open Reduction and Internal Fixation (ORIF) surgery. If not properly managed, pain can delay the healing process and increase the risk of complications. Early mobilization is a nonpharmacological intervention that can help reduce pain intensity by improving blood circulation, decreasing inflammatory mediators, and shifting the patient's focus away from pain. To determine the effectiveness of early mobilization in reducing pain levels in patients after Open Reduction and Internal Fixation (ORIF) surgery. This study used a quasiexperimental design with a pre-test and post-test approach in two groups. The sample consisted of 42 respondents. Data were collected using the Numeric Rating Scale (NRS) and analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney test. The results showed a significant decrease in pain levels in the treatment group after early mobilization was administered. The average pain level in the treatment group decreased more significantly than in the control group, which did not receive early mobilization (p 0.05). Early mobilization is proven to be effective in reducing pain levels in post-ORIF surgery patients. This intervention can be an essential part of postoperative nursing care to accelerate recovery and improve patient comfort. Keywords: Early Mobilization, Pain, Postoperative, ORIF, Nursing. ABSTRAK Nyeri pasca operasi merupakan salah satu komplikasi yang sering dialami oleh pasien, termasuk pada kasus operasi Open Reduction and Internal Fixation (ORIF). Nyeri yang tidak tertangani dengan baik dapat memperlambat proses pemulihan dan meningkatkan risiko komplikasi. Mobilisasi dini merupakan salah satu intervensi non-farmakologis yang dapat membantu menurunkan intensitas nyeri dengan meningkatkan aliran darah, mengurangi mediator peradangan, dan mengalihkan fokus pasien dari nyeri. Untuk mengetahui efektivitas mobilisasi dini dalam menurunkan tingkat nyeri pada pasien pasca operasi Open Reduction and Internal Fixation (ORIF). Penelitian ini menggunakan desain kuasi eksperimental dengan pendekatan pre-test dan post-test pada dua kelompok. Sampel berjumlah 42 responden dan analisis data menggunakan uji Wilcoxon Signed Rank dan Mann- Whitney. Hasil menunjukkan adanya penurunan tingkat nyeri yang signifikan pada kelompok perlakuan setelah dilakukan mobilisasi dini. Rata-rata tingkat nyeri kelompok perlakuan menurun secara bermakna dibanding kelompok kontrol yang tidak mendapat intervensi mobilisasi dini (p 0,05).. Mobilisasi dini terbukti efektif dalam menurunkan tingkat nyeri pada pasien post operasi ORIF. Intervensi ini dapat menjadi bagian penting dari praktik keperawatan postoperatif untuk mempercepat pemulihan dan meningkatkan kenyamanan pasien. Kata Kunci: Mobilisasi Dini, Nyeri, Post Operasi, ORIF, Keperawatan